Case report: A choroidal fissure pial arteriovenous malformation inducing venous congestive edema of the medulla oblongata and cervicothoracic spinal cord presented with proximal arm predominant weakness - Jiang, Yun; Zhou, Ying; Yang, Ximeng; Sheng, Aizhen; Lu, Jun (Frontiers in Neurology, 2023)
Intracranial dural arteriovenous fistula (DAVF) can induce remote myelopathy via spinal perimedullary venous drainage. In the present study, we report a rare case of intracranial pial arteriovenous malformation (AVM)-related myelopathy. A 52-year-old man presented with progressive, predominantly proximal weakness and muscle atrophy in bilateral upper limbs, urinary retention, and hyperreflexia in bilateral upper and lower limbs. Brain and cervicothoracic MRI showed longitudinal myelopathy extending from the medulla oblongata to the T6 level, with perimedullary enlarged veins from the C1 to T12 level, and remarkable enhancement in bilateral anterior horns from the C2 to C7 level. Cerebral angiography revealed a choroidal fissure AVM, which was supplied by the left anterior choroidal artery and drained exclusively by an inferior ventricular vein descending toward the spinal perimedullary veins. After endovascular embolization of the feeding pedicle, nidus, and proximal segment of the draining vein, the patient's neurological deficits rapidly improved, and a significant recovery was achieved 3 months after the procedure. This rare case indicates that intracranial pial AVM can also cause extensive congestive myelopathy with similar mechanisms underlying intracranial and craniocervical DAVF cases, and gray matter in the spinal cord might be more susceptible to ischemia induced by intraspinal venous hypertension.